استخدام التحليل الشبكي في جدولة المشاريع الإنشائية - تلي، سيف الدين; تقدة، خولة (المركز الجامعي أمين العقال الحاج موسى أق أخموك بتامنغست, 2022)
تهدف هذه الدراسة إلى التعرف إلى أحد أهم الأساليب الكمية في إدارة المشاريع الإنشائية والتي تساعد على تحقيق أهداف المشروع والمتمثلة في الوقت والتكلفة والجودة. ومن خلال هذه الدراسة تم إبراز أهمية استخدام التحليل الشبكي والبرامج الحاسوبية ومنها برنامج MSProject في مجال إدارة المشاريع الإنشائية، وقد تم التوصل إلى أن الوقت اللازم لتنفيذ مشروع دراسة يقدر بــ 298 يوما أي ما يقارب 10 أشهر وهي أقل بكثير من المدة التي حددتها مؤسسة الإنجاز، وهذا ما سوف ينعكس سلبا على تكلفة المشروع. This study aims to identify one of the most important quantitative methods in managing construction projects, which helps to achieve the project goals of time, cost and quality. Through this study, the importance of using net work analysis and computer programs, including the MS Project program in the field of construction project management, was highlighted, and it was reached that the time required to implement a study project is estimated at 298 days, which is approximately 10 months, which is much less than the period specified by the achievement, This will reflect negatively on the cost of the project.
Keywords: إدارة المشروعات -- القرارات الإدارية -- الأساليب الكمية -- نظم المعلومات الإدارية